Interactive Teaching: Activities and the Use of Technology in EFL Classroom - Anggeraini, Yentri (Language Circle: Journal of Language and Literature, 2018)
A variety of technologies are all around us in our homes, offices, and schools. Today, students are familiar with number of applications of computer network technology such as multimedia, email, electronic journals, databases, World Wide Web, chat, blog, audio social media and video conferencing etc. Technology plays a positive role in promoting activities and initiatives of the students in English classroom. Interactive teaching and technology put the emphasis on communication, interaction, and discussion between teachers and students as well as the positivity of teachers and students in the teaching and learning process. The fact that by providing technology and applying interactive teaching can make the students be active and creative so that the teacher should know how to provide the technology in teaching and learning process. The aim of this paper is to explore some activities in interactive teaching and provide how to apply them in EFL classroom by providing the use of technology such as digital storytelling, podcast, clipped students, conversation analysis from YouTube, apposite arguments, and Powtoon.